2013
DOI: 10.1007/s10549-013-2541-y
|View full text |Cite
|
Sign up to set email alerts
|

Fulvestrant regulates epidermal growth factor (EGF) family ligands to activate EGF receptor (EGFR) signaling in breast cancer cells

Abstract: Estrogen receptor-α (ER) targeted therapies are routinely used to treat breast cancer. However, patient responses are limited by resistance to endocrine therapy. Breast cancer cells resistant to the pure steroidal ER antagonist fulvestrant (fulv) demonstrate increased activation of epidermal growth factor receptor (EGFR) family members and downstream ERK signaling. In this study we investigated the effects of fulv on EGFR signaling and ligand regulation in several breast cancer cell lines. EGFR/HER2/HER3 phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…Additionally, in lung cancer cell lines, a recent study showed benefit of combining anti-EGFR and anti-estrogen (47). Although multiple studies have shown interaction between EGFR and ERα pathways (48, 49), further study is needed to elucidate the role of RET, EGFR, and VEGFRs in determining growth characteristics, interaction with hormone signaling pathways, and mediating the anti-tumor effects of vandetanib in luminal breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in lung cancer cell lines, a recent study showed benefit of combining anti-EGFR and anti-estrogen (47). Although multiple studies have shown interaction between EGFR and ERα pathways (48, 49), further study is needed to elucidate the role of RET, EGFR, and VEGFRs in determining growth characteristics, interaction with hormone signaling pathways, and mediating the anti-tumor effects of vandetanib in luminal breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Fulvestrant was shown to differentially regulate EGFR ligands in breast cancer cells. 28 In fact, a major mechanism of acquired resistance to endocrine therapy in breast cancer is HER2/HER3 overactivation. 29 HER2/HER3 signaling is potently induced by NRG1-b1, which is highly induced by fulvestrant in NSCLC cells, an effect that was abrogated by adding dacomitinib.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The binding of fulvestrant with ER also leads to a rapid degradation of the fulvestrant-ER complex and makes the receptor unavailable to estrogens, so the ability of ER to promote gene transcription is attenuated. 19 Endocrine therapy is known to be successful in treating most patients with advanced HR +/HER2− breast cancer; however, in many cases there is a relapse and the disease becomes refractory to such approaches. 20 There are many reasons for this resistance, but the factors involved include activation of mutations in the ESR1 gene encoding for ER; an increase in CDK4/6 activity; and upregulation of signaling pathways, such as phosphoinositide-3-kinase (PI3K)/AKT/mTOR and activated protein HER2/mitogenic kinase (MAPK).…”
Section: The Backbone: Fulvestrantmentioning
confidence: 99%